2018
DOI: 10.7897/2230-8407.099209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solid Media on Growth of Mycelia and Antibacterial Activity of Wild Macrofungi, Macrocybe Gigantea

Abstract: The present study was focused on wild pantropical macrofungi, Macrocybe gigantea (Massee) Pegler & Lodge, collected from Agumbe rain forests of Karnataka, India. The macrofungal tissues was subjected to mycelial culturing in four different solid nutritive media viz., Potato Dextrose Agar, Malt Extract Agar, Sabouraud's Dextrose Agar and Czapek Dextrose Agar. The study also evaluated the invitro antibacterial activity of ethyl acetate extract of mycelial filtrates obtained from Potato Dextrose Broth cultures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…Our results were similar with Shim et al [ 32 ] in which they found PDA medium as the suitable medium for the cultural characteristics of Cystoderma amianthinum. These results were in agreement with work of Roy & Krishnappa [ 33 ]. They used PDA, SDA, MEA and czapek dextrose agar media (CZA) for mycelial growth of Macrocybe gigantea and found PDA as the best medium for maximum mycelial growth of M. gigantea .…”
Section: Resultssupporting
confidence: 94%
“…Our results were similar with Shim et al [ 32 ] in which they found PDA medium as the suitable medium for the cultural characteristics of Cystoderma amianthinum. These results were in agreement with work of Roy & Krishnappa [ 33 ]. They used PDA, SDA, MEA and czapek dextrose agar media (CZA) for mycelial growth of Macrocybe gigantea and found PDA as the best medium for maximum mycelial growth of M. gigantea .…”
Section: Resultssupporting
confidence: 94%